2022
DOI: 10.24018/ejedu.2022.3.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Academic Integrity of Students during the COVID-19 Pandemic: A Mixed Method Analysis

Abstract: This study explored the academic integrity of tertiary students during the pandemic. Sixty-six students and nine faculty members were participants in the study. Two adapted survey questionnaires and a validated researcher-made interview guide were used to obtain pertinent data. Quantitative results revealed that most students committed academic dishonesty; however, they considered those misconducts moderate cheating. Teachers observed that students committed cheating more than once; however, they only call stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…He also underlined that the idea that "someone else will do" the student's tasks was stated. Likewise, several studies confirmed similar results that influenced students to commit such acts (Pagaddu, 2021;Frigillano, 2021;Revilla & Libre, 2022;San Jose, 2022). Even the Department of Education recognized how this factor proliferates academic dishonesty (Perez, 2021).…”
Section: Internal Influencing Factorsmentioning
confidence: 75%
See 3 more Smart Citations
“…He also underlined that the idea that "someone else will do" the student's tasks was stated. Likewise, several studies confirmed similar results that influenced students to commit such acts (Pagaddu, 2021;Frigillano, 2021;Revilla & Libre, 2022;San Jose, 2022). Even the Department of Education recognized how this factor proliferates academic dishonesty (Perez, 2021).…”
Section: Internal Influencing Factorsmentioning
confidence: 75%
“…However, San Jose (2022) noted that students prefer seeking clarifications from their peers than their teachers, which can further worsen what was already a concern between student-teacher communication. In addition, parental expectations, typically attributed to receiving passing marks or even attaining higher grades was expressed as an influencing factor among students (Pagaddu, 2021;Frigillano, 2021;San Jose, 2022). Lastly, the use of digital technology, specifically utilizing the internet to commit academic dishonesty was observed as an influencing factor since it provides students with the opportunity to commit such acts with ease (Cruz et al, 2021;Frigillano, 2021;Revilla & Libre, 2022).…”
Section: External Influencing Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid, continuous advancement of technologies that offer convenient, instant access to information has made plagiarising easier than ever, while concurrently, technology has also been developed that both impedes the detection of academic plagiarism, and uncovers it (Foltýnek et al, 2019). The widespread accessibility of literature available on the internet and the growth of online, remote learning have resulted in an increased incidence of plagiarism among students in higher education (Burgason et al, 2019;Jambi et al, 2022;San Jose, 2022), and this has been exacerbated by the necessity for remote learning during population lockdowns due to the COVID-19 pandemic. During remote learning, online assessment practices which do not have adequate control systems and breaches of academic integrity by students who feel disconnected from their university (Mendez-Ortega et al, 2021) have also perpetuated the growth in plagiarism.…”
Section: A Perfect Storm?mentioning
confidence: 99%